2022
DOI: 10.1007/s10803-022-05554-7
|View full text |Cite|
|
Sign up to set email alerts
|

“Going Mobile”-increasing the reach of parent-mediated intervention for toddlers with ASD via group-based and virtual delivery

Abstract: Evidence supports early intervention for toddlers with ASD, but barriers to access remain, including system costs, workforce constraints, and a range of family socio-demographic factors. An urgent need exists for innovative models that maximize resource efficiency and promote widespread timely access. We examined uptake and outcomes from 82 families participating in a parent-mediated intervention comprising group-based learning and individual coaching, delivered either in-person ( n = 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 54 publications
(43 reference statements)
0
20
1
Order By: Relevance
“…Though QuickStart parents were satisfied with the EI methods (MPOC) their self-reports of low–moderate confidence in their parenting competence (PSOC), an important aspect of emotional well-being, persisted over the 20 weeks. QuickStart did not have a direct focus on parenting competence, but our finding is noteworthy, given that parents’ contributions to, and their ad hoc reports of, their children's progress were positive; and that other studies have found improvements through parent training ( Brian et al, 2022b ; Iadarola et al, 2018 ). We posit that perhaps the PSOC, used as our sole measure of parent self-efficacy, could not identify all the complex aspects of our parents’ emotional experiences, to detect changes in their emotional well-being, over the 20 weeks (e.g., Karp et al, 2015 ; Wittkowski et al, 2017 ).…”
Section: Discussionmentioning
confidence: 50%
“…Though QuickStart parents were satisfied with the EI methods (MPOC) their self-reports of low–moderate confidence in their parenting competence (PSOC), an important aspect of emotional well-being, persisted over the 20 weeks. QuickStart did not have a direct focus on parenting competence, but our finding is noteworthy, given that parents’ contributions to, and their ad hoc reports of, their children's progress were positive; and that other studies have found improvements through parent training ( Brian et al, 2022b ; Iadarola et al, 2018 ). We posit that perhaps the PSOC, used as our sole measure of parent self-efficacy, could not identify all the complex aspects of our parents’ emotional experiences, to detect changes in their emotional well-being, over the 20 weeks (e.g., Karp et al, 2015 ; Wittkowski et al, 2017 ).…”
Section: Discussionmentioning
confidence: 50%
“…37,52,66,69 Interventions delivered virtually have promise. 37,70 Table 2 summarises considerations that should guide interventions.…”
Section: Resultsmentioning
confidence: 99%
“…There is up and coming literature displaying the acceptability and feasibility of mHealth for children with attention deficit hyperactivity disorder (ADHD), and for caregivers of autistic individuals. 42 44 A new app, currently called My Health Coach, is also under development for adults with FASD with community member input suggesting high acceptability. 45 …”
Section: Discussionmentioning
confidence: 99%